Project management: should lawyers learn it? - Wan Hussain, Wan Mohd Hirwani; Che Mohd Zain, Che Rosmawati; Ab Rahman, Mohd Nizam; Ismail, Ahmad Rasdan; Yaakub, Noor Inayah (Conference Master Resources, 2012)
The majority of the project management literature focusing on the manufacturing, civil and industrial management process but very few have analyzed the important of the project management for lawyers. The aim of this paper is to shed some light on the project management course to the lawyers. We try to open the 'black box' by combining the manufacturing principles into the legal services industry that will help sustaining the legal profession in the future. This paper highlights the practicality of project management courses for the lawyer as the mechanism for managing their business and handling case from their client. However, the literature on project management for lawyers is incoherent, even inchoate and lacks theoretical models that reflect upon particular context of the legal industry. This paper suggests that there is still needs more research done to get a deep understanding about this issue.